Ethical Challenges of Information Systems in the Era of Digital Transformation - Annisa Nur Sabrina; Muhammad Irwan Padli Nasution (Young Journal of Social Sciences and Humanities, 2025)
The rapid development of information systems in the digital era has significantly transformed the way individuals, organizations, and societies manage, store, and distribute information. The use of advanced digital technologies not only accelerates data exchange across borders but also introduces complex ethical challenges that require serious attention. Issues such as privacy violations, inadequate data protection, digital plagiarism, misinformation, and the misuse of personal information have become increasingly prominent as digital systems continue to evolve. This study aims to examine the relationship between the advancement of information systems and the rising ethical issues that accompany global digitalization. The research relies on a review of academic literature and international business practices to understand how ethical considerations shape the management of modern information technologies. The findings indicate that the integration of strong ethical principles in information system management is crucial for ensuring responsible, transparent, and sustainable technological development. To achieve this, high ethical awareness and comprehensive regulatory policies are needed so that information technology can provide maximum benefits without compromising moral responsibilities or humanitarian values. Strengthening digital ethics is essential for building trust, safeguarding user rights, and supporting a more accountable digital future.